A Review of Heracleum Rigens, Eryngium Foetidum l., Passiflora Subpeltata Medicinal Plants: Exploring the Chemical Contents and Therapeutic Potential of Medicinal Plants (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Traditional medical practices have relied on the healing qualities of medicinal plants for ages.Heracleum rigens, Eryngium foetidum L., and Passiflora subpeltata have been singled out for their uniquemedicinal qualities and historic use from among the many plants with potential medical advantages.Insights into the chemical contents, traditional applications, and therapeutic potential of the medicinalherbs Heracleum rigens, Eryngium foetidum L., and Passiflora subpeltata may be gained via asystematic study of these species.